Base Nacional Comum Curricular e docência: discursos e significações - Rocha, Nathália Fernandes Egito (2019)
The National Curricular Common Base (NCCB) was widely discussed in the last three years (2015-2018) through numerous debates on curricular policies. The NCCB is a document of normative character that by justifying to guarantee the learning rights of Brazilian students, determines a set of "essential learning". In this thesis, we propose to investigate what are the meanings of the teaching that pervades the NCCB and how they are interpreted by the teachers. We assume that the NCCB is characterized as a normative and performative curriculum, which has the potential to deprofessionalize the teachers and introduces them into a rationalistic and unreflective logic, impairing their autonomy. On the other hand, we consider that what is developed in schools, especially by teachers, extrapolates the boundaries and propositions of curricular policy. Therefore, we aim to analyze what are the relationships between NCCB curriculum policy discourses and schoolteacher‟s discourses and to what extent these meanings translate the identities and actions taken by teachers. Methodologically, through a qualitative and exploratory approach, we carried out a documentary and field study in three schools of João Pessoa, Paraíba. We organized a focus group to collect the data, and based on the methodological theoretical framework of Stephen Ball (1992; 1994; 2001; 2016) and Norma Fairclough (2001), we analyzed the collected data. We realize that, while recognizing that the NCCB projects performative identities in teachers, both regarding rhetoric and policy strategies, these identities are not limited to this. Diverse and simultaneously, they are constructed in the daily life of the school and through the subjectivity of the people involved. Finally, we highlight the need to strengthen the debate about the autonomy in curricular decisions and the democratic management of the school, as a way to resist the culture of performativity and managerialism.